Evaluation and Economic Analysis of Some Integrated Pest Management Packages for Suppressing Tube Spittle bug (Machaerota planitiae Distant) Infesting Jujube (Zizyphus mauritiana Lamk), in North-Western Bangladesh (The Agriculturists, 2016)
To develop a suitable integrated pest management (IPM) package(s) against tube spittle bug attacking jujube, the study was conducted at the farmers orchard at Sherpur Upazilla of Bogra district, Bangladesh during the two consecutive winter seasons of 2011-12 and 2012-13. There were five IPM packages viz., P1 = Clean cultivation + collection and destruction of tube with alive nymph from the branches, P2 =P1 + two sprays of Detergent @ 2gl-1 of water applied (at initial stage of infestation and 10 days after 1st spray), P3 =P1 + two sprays of crushed Neem seed extract @ 150 gl-1 of water (at initial stage of infestation and 10 days after 1st spray), P4 =P1 + sprays of Cypermethrin @ 1 mll-1 of water at initial stage of infestation, P5 =P4 + one additional spray of Cypermethrin @ 1mll-1 at 10 days after 1st spray and an untreated control. In both the years, treatment P5 was found most effective, which resulted lower damage to inflorescence and produced higher yield, followed by P4 and P3.  In case of marginal benefit cost ratio, the highest value (15.69 & 20.63) was obtained from the treatment P5 which was closely followed by P4 (15.07 &20.12) in both of years, respectively.The Agriculturists 2016; 14(1) 54-62